1985
DOI: 10.1136/jnnp.48.7.676
|View full text |Cite
|
Sign up to set email alerts
|

Chronic transformation of muscle in spasticity: a peripheral contribution to increased tone.

Abstract: SUMMARY Mechanical properties of relaxed lower leg muscles were assessed by torque measurements during imposed constant velocity dorsiflexion-plantarflexion cycles. At low angular velocities, they exhibited an elastic and an energy-consuming, velocity-independent (plastic) resistance. In most patients with long-standing spasticity, both of these were enhanced. The results support the hypothesis of secondary structural changes of muscles in spasticity.Spastic increase of muscle tone is estimated by the resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
6

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(106 citation statements)
references
References 27 publications
3
97
0
6
Order By: Relevance
“…Torque motor experiments applied to upper and lower limb muscles indicate a major, non-re¯ex contribution to the spastic muscle tone in the antigravity muscles, ie, in the leg extensors and elbow¯exors. 42,43 Histochemistry and morphometry studies of spastic muscle have revealed neurogenic changes of the muscle ®bres. 14,36 These include: (a) increased levels of muscle ®bre atrophy (especially of type II ®bres); (b) a predominance of type I ®bres in the gastrocnemius during later stages, when spasticity of cerebral origin has been established; (c) structural changes, such as the appearance of target ®bres, mainly in type I ®bres and (d) a signi®cant part of changes of mechanical muscle ®bre properties may be attributed to a shortening of muscle length as a result of a decrease in the number of sarcomeres in series along the myo®brils accompanied by an increase in resistance to stretch.…”
Section: Motor Unit Transformation and Spastic Muscle Tonementioning
confidence: 99%
“…Torque motor experiments applied to upper and lower limb muscles indicate a major, non-re¯ex contribution to the spastic muscle tone in the antigravity muscles, ie, in the leg extensors and elbow¯exors. 42,43 Histochemistry and morphometry studies of spastic muscle have revealed neurogenic changes of the muscle ®bres. 14,36 These include: (a) increased levels of muscle ®bre atrophy (especially of type II ®bres); (b) a predominance of type I ®bres in the gastrocnemius during later stages, when spasticity of cerebral origin has been established; (c) structural changes, such as the appearance of target ®bres, mainly in type I ®bres and (d) a signi®cant part of changes of mechanical muscle ®bre properties may be attributed to a shortening of muscle length as a result of a decrease in the number of sarcomeres in series along the myo®brils accompanied by an increase in resistance to stretch.…”
Section: Motor Unit Transformation and Spastic Muscle Tonementioning
confidence: 99%
“…"Easy-todifficult" sequence in terms of progressively decreasing robotic support, determined by stiffness setting: K (Nm/rad), is same for each visit throughout training, but task difficulty in terms of vertical location of targets (challenging AROM) and speed of targets (challenging speed of ankle targeting) on screen are adjusted in weeks 3-4 and 5-6, respectively, based on prior subject performance in order to provide challenge where applicable (at least sustained 80% targeting success without robotic assistance in weeks 1 and 2) and sustain subject motivation. and ramp down) was to avoid evoking stretch reflex, as reported in other studies [15,19,[34][35]. Under the relaxed condition, subjects experienced a series of perturbations during which the ankle was stretched to a commanded position, held at steady state for 1 s, and returned to neutral.…”
Section: Stiffness Measurementmentioning
confidence: 99%
“…In fact, the manifestation of increased motor neuron excitability and an increased resistance to passive movement have been observed in clinical assessments [14][15][16][17][18]. In addition, structural changes of muscle fibers and connective tissue may contribute to alterations in the intrinsic mechanical properties, e.g., stiffness of a joint.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of disuse of the peripheral motor apparatus could be excluded, because all patients in this study walked independently and were on a series of therapeutic exercises, and moreover, TLT of their non-affected side was not different from that of the normal subjects. Hufschmidt and Mauritz (1985) reported that the enhancement in elastic and plastic resistance of the spastic muscle. Such changes, however, occurred more than one year after the onset of disease in their study.…”
Section: Discussionmentioning
confidence: 99%